A new vasculitis at the time of COVID-19. - Mazzotta, F.; Troccoli, T.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
The authors describe a vasculitis observed for the first time during the COVID-19 pandemic, which affected children towards the end of the first decade of life and teenagers, however, in good health, prevailed on the feet and resembled chilblains, but in the absence of exposure to the cold and predisposing constitutional factors. When it was possible to perform swabs and serological tests these were often negative; the probable relationship with COVID-19 was based on the history, on the concomitance between lesions never observed previously and a new infection, on the presence of vasculitic lesions of the same type but much more serious in patients with severe forms of COVID-19.